Pengaruh Pesan Pemasaran Melalui Media Sosial “Instagram” Terhadap Minat Beli Produk Di CV Tirta Fertindo Pratama - Wati, Anista; Gayatri, Siwi; Mariyono, Joko (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
This study aimed to analyze the influence of marketing messages that were delivered by CV Tirta Fertindo Pratama through social media Instagram on consumer purchase intention. The research was conducted on the Instagram account @fertindo_semarang. The research method in this study was a case study method with a Non-Probability Sampling technique. The sample consisted of 100 respondents, who were followers of the @fertindo_semarang Instagram account. The data analysis method that was applied in this study was quantitative analysis using multiple linear regression analysis. The results of the study showed that the variables message structure (X1), message format (X2), message content (X3), message source (X4), age (X5), and education (X6) simultaneously had a significant effect on purchase intention (Y). These six independent variables contributed 75.4% to the dependent variable, which was purchase intention. In the partial test (t-test), the findings revealed that structure, format, and content of the social media of @fertindo_semarang had a positive and significant influence on purchase intention. Message source had a positive but not significant influence. Age had a negative and did not significant influence on purchase intention. Education had a negative but had significant influence on purchase intention. The variable that had the most dominant influence on purchase intention was message content, as it had the lowest significance value and the highest beta coefficient.